Formulasi Sediaan Masker Lumpur Dari Ekstrak Daun Sirsak (Annona Muricata L.) Untuk Mencerahkan Wajah - Khairina Khairina; Rosa Mardiana; Sasmiati Farach Dita; Lidyawati Lidyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Face masks are a form of facial treatment that have been found traditionally to clean pores and improve facial skin, one of which is a mask made from soursop leaf extract. Soursop leaf is one of the cosmetic ingredients for dull skin care which is used as a mask to brighten the face. The content found in soursop leaves include phenolic compounds, alkaloids, and essential oils. This research is an experimental research, using a predetermined formula and carried out several tests such as: homogeneity, spreadability, pH, and irritation. The results of the formulation of the mud mask preparation from soursop leaf extract (Annona muricata L.) showed that F0, FI and FII gave good results. The results of the homogeneity examination showed that F0, FI and FII were homogeneous. The results of the dispersion test showed results that looked good, namely 6-7 cm. F0, FI and FII have the same pH of 7 and are in accordance with the pH that can be tolerated by the skin, as well as for the irritation test when the F0, FI, and FII preparations were tested on test volunteers did not cause irritation